Modulation of innate and adaptive immune responses by intranasally delivered adjuvants - McNeela, Edel (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2002)
Vaccines have had a significant impact on human health for over a hundred years, resulting in the prevention of many millions of deaths each year from infectious diseases. However in recent decades, the evolution of antibiotic resistant strains of bacteria, the emergence of new pathogens and widespread concerns over the safety of traditional vaccines have highlighted the requirement for the continued development and improvement of vaccination strategies. Alternatives to parenteral routes of vaccine delivery, such as intranasal immunization, may increase patient compliance and may assist in the elimination of pathogens that replicate on or enter via mucosal surfaces due to the induction of local immunity. New generation vaccines, based on recombinant proteins or DNA, are likely to be less reactogenic than traditional vaccines composed of live attenuated or killed pathogens or inactivated toxins. However, these vaccines are often less immunogenic, especially following mucosal delivery. There is therefore an urgent requirement for the development of potent and safe adjuvants that are effective for mucosal immunization.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin